A Human Milk–Based Protein Concentrate Developed for Preterm Infants Retains Bioactive Proteins and Supports Growth of Weanling Rats - Shama, Sara (J Nutr, 2021)
BACKGROUND: Bovine milk–based protein modulars are currently available to nutrient-enrich enteral feedings; however, they have limitations for use in very-low-birth-weight infants. OBJECTIVES: Our objectives were to develop a human milk–based protein (HMP) concentrate and to conduct a preclinical assessment of the HMP concentrate in weanling rats. METHODS: An HMP concentrate was produced from donor milk using pressure-driven membrane filtration processes and high hydrostatic pressure processing. Protein and lactoferrin concentrations and lysozyme activity were determined by Kjeldahl, HPLC, and turbidimetric assay, respectively. Male Sprague Dawley rats 24 d old (n = 30) were randomly assigned to 1 of 3 isocaloric AIN-93G diets for 4 wk containing 100% casein (control) or with 50% of the casein replaced with the HMP concentrate (treatment) or a bovine whey protein isolate (treatment). Body weight, food intake, fat mass, plasma amino acid profiles, and organ weights were measured. Data were analyzed using linear regression models. RESULTS: Raw donor milk contained (mean ± SD) 101 ± 6 g protein/kg and 5 ± 1 g lactoferrin/kg of milk solids. Postprocessing, protein and lactoferrin concentrations were 589 ± 3 g/kg and 29 ± 10 g/kg, respectively. Lysozyme activity was initially 209 ± 4 U/kg and increased to 959 ± 39 U/kg in the HMP concentrate. There were no statistically significant differences in body weight, food intake, fat mass, or plasma amino acid profiles between rats fed diets containing the HMP concentrate and the control diet. Full cecum weights were higher in rats fed the HMP concentrate than in those fed control diets (mean difference: 5.59 g; 95% CI: 4.50, 6.68 g; P < 0.0001), likely reflecting the concentration of human milk oligosaccharides. No differences were found for other organ weights. CONCLUSIONS: The HMP concentrate retained important bioactive proteins and supported normal rat growth in the preclinical assessment.